O estabelecimento de Paspalum repens P. J. Bergius (Poaceae) é positivamente afetado pela mudança do nível d’água, mas negativamente afetado pela densidade de uma macrófita invasora e pela riqueza de espécies. - Vicente, Abner José de Souza (2022)
Changes in water level influence the establishment and ecological interactions developed between aquatic macrophytes.With the aim of investigate how changes in water level, the density of the invasive macrophyte Urochloa arrecta and the species richness influence the establishment of Paspalum repens, we set up two experiments in a greenhouse with three water levels (high, medium and static) and two levels of density and species richness. At the end of the experiments, we measured the following response variables: leaf area surface, shoot biomass, root biomass, total biomass, shoot length, and root length of P. repens. Using the total biomass, we calculated the relative interaction index (RII) to verify the type of ecological interaction developed between P. repens and its neighbors species. Each response variable was analyzed with a two-way ANOVA. Among the results obtained, we highlight: i) the predominantly negative values of the RII, indicating competition between P. repens and its neighbors in all the conditions tested in this work and ii) positive values of leaf area surface and shoot biomass at water levels high, especially in the experiment that analyzed the effect of the density of U. arrecta on P. repens, which highlights the strategies adopted by this species to establish itself in environments with high densities of the invasive species in scenarios of water level changes. Finally, these results indicate the effects of changes in water level, density of U. arrecta and species richness on P. repens, contributing to the understanding of the dynamics of macrophyte communities in freshwater ecosystems.